Nutritional Characterization of Diacylglycerols in Rats - WATANABE, Hiroyuki; MATSUO, Noboru; CHIBA, Hiroe; KOBORI, Mayumi; TAGUCHI, Hiroyuki; HATTORI, Michihiro; YASUKAWA, Takuji; NAITO, Sachio; SHIMASAKI, Hiroyuki; ONIZAWA, Kouji (Journal of Japan Oil Chemists' Society, 1997)
Diacylglycerols (DG) are lipids which influence to a lesser extent the increase of the concentrations of triacylglycerols (TG) in serum by ingestion. The nutritional characteristics of DG consisting of 1, 3-DG and 1, 2-DG species were investigated in rats. Digestic and metabolic process in DG and TG were found to differ significantly. 1) 1-Monoacylglycerols (MG), rarely seen in the digest of TG in the intestine, were mainly produced from DG. 2) Greater amounts of fatty acids were released from intestine into the portal vein after the administration of DG, compared to TG. 3) DG ingestion enhances the β-oxidation of fatty acids in the liver and released ketone bodies into the urine. 4) Increase in oxygen consumptions by DG was greater than by TG in rats. DG would thus appear to be an ideal source of energy, making possible less fat accumulation compared to TG.